Virginia Berridge & Philip Strong (eds.): AIDS and Contemporary History - Dahl, Anders (Tidsskriftet Antropologi, 2019)
Virginia Berridge & Philip Strong (eds.): AIDS and Contemporary History Anmeldes af Anders Dahl